RAMIFICATIONS OF ROADWAYS CONDITIONS AND TRAFFIC FEATURES ON ROADS SAFETY: A SAFETY PERSPECTIVE FOR JALANDHAR, PUNJAB (INDIA) - Kushagra Pandey, P.S. Charpe (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
India is in a developing phase and safety on roads is at a premature stage. Accidents are increasing day by day leading to a great loss of life. Some have disablements, other damage to property and health, and degradation of environment resulting in a situation in India that is at a tocsin stage. Official records show that approximately 1, 42,000 persons were killed and approximately 4, 80,000 injured in traffic accidents in India in 2014 (NCRB 2015). However, this is underestimated since many accidents are off the records also, as all accidents are not reported. This higher accident rate is due to inadequacy of highways and GT roads which cannot meet the traffic demands or some other reasons like vehicular defect, poor road geometry or road user behavior. These accidents deal a heavy blow to the economy of a country. Hence, road safety is a necessity for reduction in accidents